2017
DOI: 10.1097/md.0000000000006087
|View full text |Cite
|
Sign up to set email alerts
|

Rapid intracranial response to osimertinib, without radiotherapy, in nonsmall cell lung cancer patients harboring the EGFR T790M mutation

Abstract: Rationale:Most of nonsmall cell lung cancer (NSCLC) patients harboring epidermal growth factor receptor (EGFR) activating mutations eventually acquire resistance to the first EGFR-tyrosine kinase inhibitors (TKIs) therapy after varying periods of treatment. Of note, approximately one-third of those patients develop brain metastases, which deteriorate their quality of life and survival. The effect of systemic chemotherapy on brain metastases after acquisition of EGFR-TKI resistance is limited, and thus far, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…First, it penetrates the bloodbrain barrier very well ( Figure 1A). While our studies were on mice, osimertinib has been shown elsewhere to penetrate the human brain as well [19,[24][25][26][27]. Second, osimertinib is an irreversible inhibitor of EGFR tyrosine kinase, so its inhibition of EGFRvIII signaling is longlasting.…”
Section: Discussionmentioning
confidence: 91%
“…First, it penetrates the bloodbrain barrier very well ( Figure 1A). While our studies were on mice, osimertinib has been shown elsewhere to penetrate the human brain as well [19,[24][25][26][27]. Second, osimertinib is an irreversible inhibitor of EGFR tyrosine kinase, so its inhibition of EGFRvIII signaling is longlasting.…”
Section: Discussionmentioning
confidence: 91%
“…Several cases of LM treated with osimertinib have been reported. Koba et al 19 observed a rapid response to osimertinib, within 2 weeks of its administration in patients with brain metastases. Hata et al 20 observed that osimertinib efficiently passes the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…In the preclinical study, osimertinib demonstrated greater penetration of the mouse blood-brain barrier than gefitinib, rociletinib, or afatinib [ 94 ]. There were several reports of dramatic intracranial response to osimertinib in patients with EGFR T790M lung cancer [ 94 , 95 ]. A phase I study (BLOOM, NCT02228369), which has enrolled pretreated EGFR -mutant NSCLC patients with leptomeningeal metastasis treated with 160 mg osimertinib once daily, is ongoing.…”
Section: Introductionmentioning
confidence: 99%